PENGARUH MENTAL ACCOUNTING, LITERASI PERPAJAKAN, DIGITALISASI PERPAJAKAN, DAN MEDIA SOSIAL TERHADAP KEPATUHAN PAJAK ORANG PRIBADI - Abdullah Ulmi Zuhdhan Fanani; Anggoro, Rusmawan Wahyu (LPPM STIE YKPN Yogyakarta, 2025)
Taxpayer compliance is one of the key aspects of the success of state financial management. However, the level of taxpayer compliance that has not met the target remains a challenge. This study aims to examine the influence of mental accounting, tax literacy, tax service digitalization, and social media on the intention of individual taxpayer compliance. The research adopts a quantitative approach and is analyzed using multiple linear regression analysis. The population of this study consists of individual taxpayers, with a sample size of 153 determined using the purposive sampling method. The results indicate that mental accounting, tax service digitalization, and social media positively affect the intention of individual taxpayer compliance, while tax literacy has no effect on the intention of individual taxpayer compliance.